2015
DOI: 10.1016/j.sbspro.2015.01.407
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Cultures Integration and Organizational Performance: A Conceptual Model on the Performance of Acquiring Companies

Abstract: Mergers and Acquisitions (M&A) is one of the corporate strategies for companies to achieve better performance. However, it have been reported that many companies fail to meet the expected synergy value. Through an extensive review of related literatures and interview with key executives experienced with M&A, corporate cultures integration has been identified as a critical factor in success and failure of M&A exercises. A conceptual model was developed to describe its relationship with organizational performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Corporate managers can establish an effective organizational culture to enhance performance (Childress, 2013;Flamholtz & Randle, 2011;Melo, 2012). Efficacious cultural integration within the corporate group is an important element in maintaining successful communication and enhancing performance (Idris, Wahab, & Jaapar, 2015). Lee and Gaur (2013) indicated that establishing an effective organizational culture in the corporate group is necessary to enhance performance.…”
Section: Organizational Culture Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Corporate managers can establish an effective organizational culture to enhance performance (Childress, 2013;Flamholtz & Randle, 2011;Melo, 2012). Efficacious cultural integration within the corporate group is an important element in maintaining successful communication and enhancing performance (Idris, Wahab, & Jaapar, 2015). Lee and Gaur (2013) indicated that establishing an effective organizational culture in the corporate group is necessary to enhance performance.…”
Section: Organizational Culture Ismentioning
confidence: 99%
“…Profitability is a crucial factor for the persistence of any business, and expanding the business scope is also vital for the growth of the business (Erdorf, Hartmann-Wendels, Heinrichs, & Matz, 2013). Poor cultural integration within diversified companies affects the financial performance of the corporate group and shareholder value (Eaton & Kilby, 2015;Idris et al, 2015). Weber and Tarba (2012) Weber and Tarba (2012) indicated that 89% of newly acquired businesses in the United States of America fail to succeed due to a lack of cultural integration between member companies and the corporate office.…”
Section: Manymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have determined that OC emerges as one of the principal drivers for post-merger performance (Ali et al, 2018;Denison, 1993;Denison et al, 2011;Gupta, 2011;Idris et al, 2015). Other extensive research studies focus on how cultural differences affect the level of integration (Chatterjee et al, 1992;Child et al, 2001;Pitkethly et al, 2003;Weber, 1996;Weber et al, 1996;Weber et al, 2011).…”
Section: Organisational Culture and Mergers And Acquisitionsmentioning
confidence: 99%
“…Introduced as a mainstay in the submitted M&A research (Denison et al, 2003;Weber et al, 1996), organisational culture (OC) appeared at one time to be a focal area in respect of links with M&A performance in a large and growing number of publications (Denison et al, 2011;Giessner et al, 2016;Hu et al, 2009;Idris et al, 2015;Scott et al, 2003;Verdu-Jover et al, 2018). Yet, there is little research assessing the impact of OC on integration levels in the newly merged organisation.…”
Section: Introductionmentioning
confidence: 99%